Unmanned Aerial Vehicles Swarm for Protecting Smart Cities Future Trends and Challenges - Arshi, Oroos (Apress, 2025)
Explore the intersection between unmanned aerial vehicles (UAVs) and the evolving landscape of smart cities. With the increasing integration of technology into urban environments, there is a growing need to understand how UAV swarms can contribute to the safety, efficiency, and resilience of these complex urban ecosystems. The book aims to provide a technical understanding of UAV swarms and their applications within the context of smart cities. It begins by laying the groundwork with an introduction to UAV swarms and smart cities, establishing the foundational concepts and motivations behind their integration. As the book progresses, it delves into various aspects of smart cities, exploring concepts, technologies, and challenges inherent in their development and operation. This includes discussions on cloud computing, cybersecurity, machine learning applications, surveillance and monitoring systems, urban planning, and infrastructure management.